2018
DOI: 10.3390/molecules23123333
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Research Reveals the Mechanism of Action of Astragalus Polysaccharide in Rats with Digestive System Disorders

Abstract: With the diversity of modern dietary lifestyles, digestive system disorders (DSD) have become a frequently occurring disease in recent years. Astragalus polysaccharide (APS) is a homogeneous polysaccharide extracted from Astragalus, which might ameliorate the digestive and absorptive functions. However, the treatment mechanisms remain unclear. In this study, rats with DSD were fed a high-fat–low-protein diet and subjected to weight-bearing swimming until exhaustion. When body weight and autonomous activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The lipid metabolites (for instance triglycerides) that stored in cells and cell membranes were degraded to release fatty acids to meet the energy needs of the body. 20 What's more, large amounts of fatty acids could induce oxidative stress and further aggravate the intestinal inflammation. 21 And dysregulated lipid metabolism also affected sugar metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The lipid metabolites (for instance triglycerides) that stored in cells and cell membranes were degraded to release fatty acids to meet the energy needs of the body. 20 What's more, large amounts of fatty acids could induce oxidative stress and further aggravate the intestinal inflammation. 21 And dysregulated lipid metabolism also affected sugar metabolism.…”
Section: Resultsmentioning
confidence: 99%
“… 16 Wang et al proved that AR polysaccharide could ameliorate the digestive and absorptive functions by serum metabolomics. 17 Zeng et al reported that AR polysaccharide regulated the energy metabolism of heat stressed dairy cows through glucose metabolism and amino acid metabolism. 18 Metabolomics is therefore a desirable technique to study the immunomodulatory mechanism of AR ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Modern instrumental analysis methods such as nuclear magnetic resonance spectroscopy and mass spectrometry allow qualitative and quantitative detection of endogenous and exogenous metabolites in biological fluids. As such, metabolomics analyzes life phenomena by establishing a more holistic view which could provide opportunities for cross-referencing in multiple directions in the medical field [17][18][19].…”
Section: Introductionmentioning
confidence: 99%